Biofortification of Wheat Cultivars to Combat Zinc Deficiency - Chattha, Muhammad U.; Hassan, Muhammad U.; Khan, Imran; Chattha, Muhammad B.; Mahmood, Athar; Chattha, Muhammad U.; Nawaz, Muhammad; Subhani, Muhammad N.; Kharal, Mina; Khan, Sadia (Frontiers in Plant Science, 2017)
Zinc (Zn) deficiency caused by inadequate dietary intake is a global nutritional problem in human populations, especially in developing countries. Therefore, Biofortification of wheat and other cereal crops is an urgent challenge and high-priority research task. A field study was planned to evaluate the influence of zinc application on grain yield, grain zinc and grain phytic acid concentrations of wheat cultivars. In this study, we also examined the relationships between grain yield, grain zinc and grain phytic acid concentration. Three wheat cultivars, i.e., C1=Faisalabad-2008, C2=Punjab-2011 and C3=Millet-2011 were tested with five different zinc application methods, i.e., T1=control, T2=seed priming, T3=soil application, T4=foliar application and T5=soil+foliar application. We found that grain yield and grain zinc were positively correlated, whereas, grain phytic acid and grain zinc were significantly negatively correlated. Results also revealed that soil+foliar, soil and foliar application alone considerably increased the grain yield; however, seed priming slightly enhanced the grain yield. Grain zinc concentration increased from (33.1, 33.7 mg kg-1) at control to (62.3, 63.1 mg kg-1) at soil+foliar application in 2013-14 and 2014-15 respectively. Zinc application methods, especially, soil+folair application markedly decreased the grain phytic acid contents, however, the maximum grain phytic acid concentration was recorded with no zinc application. Moreover, all the tested cultivars also had considerable variations for the grain yield, grain zinc and grain phytic acid contents. Conclusively, soil+foliar application of zinc is suitable for the optimum grain yield and grain bio-fortification of wheat.